PENGEMBANGAN MEDIA ANIMASI VIDIO VISUAL UNTUK PEMBELAJARAN MATERI BENCANA ALAM DI SEKOLAH DASAR - Agus Sunyoto; Yusni Arni; Tantri Pranuwita; Nina Haifa Hafifah; Anti Amalia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to explore how the use of learning media in the form of animated videos can help students in mastering the material delivered by the teacher during the learning process. This media also strongly supports the role of teachers in delivering material, especially on the topic of natural disasters in science learning for elementary school level IV students. With this media, students will also prefer to follow the learning process in the classroom because elementary school students prefer different and fun learning methods. With this kind of learning media, schools must have adequate facilities and infrastructure so that all teachers can apply video animation learning media or other learning media using communication tools.